Pengembangan Karakter, Literasi Bahasa Inggris, dan Kesadaran Kesehatan di Kalangan Siswa Sekolah Dasar melalui Program Pendidikan Terpadu di SD Negeri Sutopati 3 Magelang, Jawa Tengah - Mukti, Titania; Sabatini, Mirela; Rohma, Meisya (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Elementary school is a crucial phase in shaping children’s character, healthy lifestyle habits, and the development of basic skills, including literacy and health awareness. SDN Sutopati 3, located in Sukomakmur Village, Kajoran District, Magelang Regency, faces several challenges, particularly the low level of students’ awareness of Clean and Healthy Living Behavior (PHBS), limited basic English proficiency, and low learning motivation and future aspirations. The region’s cold geographical conditions also influence students’ habits, such as the lack of routine morning bathing and tooth brushing, which affects dental health and personal hygiene. This community service activity aims to improve students’ awareness of PHBS, basic English skills, as well as their motivation and aspirations through an integrated educational program based on local wisdom. The method used is a participatory and educational approach with an experiential learning strategy, including PHBS education through demonstrations and hands-on practice, game- and storytelling-based English learning, and motivational activities through the creation of a “dream tree.” The program actively engages students in an interactive, contextual, and enjoyable learning process. The results show an increase in students’ understanding and awareness of the importance of personal hygiene, improved confidence in using simple English vocabulary, and the growth of learning motivation and awareness of the importance of having aspirations. The integration of local wisdom values in the activities also strengthens students’ acceptance of the material presented. Therefore, this program has proven effective in strengthening character, health, and literacy among elementary school students. Sustained implementation of the program through support from schools and families is essential to ensure its long-term impact.